2021
DOI: 10.30564/jmser.v3i2.2613
|View full text |Cite
|
Sign up to set email alerts
|

Online Shopping: Antecedents of Attitude, Intention and Use

Abstract: Consumer behavior in electronic commerce has been the theme of hundreds of studies conducted by researchers of many nationalities in the past twenty years. The purpose of this study was to review and classify the concepts used in papers published between 2003 and 2014 to explain the consumer behavior in electronic commerce. A systematic search of the literature in nine databases was performed and 136 papers published in double-blind peer reviewed journals were selected. Reference models were prepared based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Behavior Intention. Several factors influence consumers' behavioural attitudes, including individual characteristics, user behaviour, user experience, user perceptions, and other external factors (Wilnei Aldir & Rafael, 2021). Attitudes towards behavioural intention show the most significant positive correlation (Wang et al, 2023).…”
Section: Attitude Subjective Norms Perceived Behavioral Control and P...mentioning
confidence: 99%
“…Behavior Intention. Several factors influence consumers' behavioural attitudes, including individual characteristics, user behaviour, user experience, user perceptions, and other external factors (Wilnei Aldir & Rafael, 2021). Attitudes towards behavioural intention show the most significant positive correlation (Wang et al, 2023).…”
Section: Attitude Subjective Norms Perceived Behavioral Control and P...mentioning
confidence: 99%
“…Attitude toward a behavior refers to one's positive or negative feeling about performing that behavior (Ajzen and Fishbein, 2000): This attitude-behavioral intention relationship shows that users with positive perception of using the technology would show higher possibility to use the technology. Researchers have found positive effects of older adults' attitude on intention to use technology including online apparel shopping (Aldir and Rafael, 2020), smart home technologies (Tural et al, 2021) and smart health wearable devices technology (Jeng et al, 2022). Also, a study by Wu and Song (2021) found a significant positive relationship between attitude and intention of older adults in the United States to use online shopping based on the TAM.…”
Section: Attitude and Behavioral Intentionmentioning
confidence: 99%
“…We point out that many factors precede the formation and the change of attitudes and online purchase intentions. Among these factors, we cite the advantages and benefits provided by online shopping, trust, ease of use, security and privacy, saving time, and website design, which were derived from previous studies, such as (Comi & Nuzzolo, 2016;Crocco et al, 2013;Naseri et al, 2021;Schneider & Tezza, 2020;Shergill & Chen, 2005).…”
Section: Online Purchase Intentionmentioning
confidence: 99%
“…Figure 1 : Research FrameworkThe model was designed based on the previous analysis and related work such asDani (2017),Naseri et al (2021),Schneider & Tezza (2020), andLi & Zhang (2002). The proposed model included the following variables: first, the independent variable represented by the factors (shopping convenience, Time-Saving, Privacy, and website design).…”
mentioning
confidence: 99%